A Karakter Maskot Sebagai Alat Pendukung City Branding Berbasis Budaya Kota: Studi Kasus Kota Ponorogo - Setya Putri Erdiana; Dhika Yuan Yurisma (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
City branding strategy is one strategy that is widely used by many cities to develop and improve public perception of a city, besides that this strategy can help promote existing potential. One of them is the City of Ponorogo which uses its traditional arts to become the image of the city, but this image is often perceived as mystical and scary. The purpose of this research is to design a mascot design, as a tool for city branding strategy. The method used is Design Research Methodology, with the design stage exploring the message to be conveyed, giving a name, designing visually, and implementing it. The results of the analysis get a mascot character with a humble, fun, and friendly impression. The mascot is named Si Bar which is derived from the representation of the main character in the traditional arts of Ponorogo City. The purpose of making this mascot is to reduce public perception regarding the Reog Ponorogo art as an image of the city.